PENGARUH LUMATAN DAUN PLETEKAN (Ruellia Tuberosa L) TERHADAP LAMA PENUTUPAN LUKA PADA TIKUS PUTIH (Rattus Novergicus) - Susana, Ria; Agustina, Rismia; Wahid, Abdurahman (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
Wounds is defined as disruption of the function and integrity of body tissues. Wound healing isa complex process of tissue repair and remodelling in response to injury. Pletekan (ruelliatuberosa l) contains flavonoids, glycosides, phenols, saponins and nutritive value that suppose toaccelerate wound healing. The purpose of this study was to identify the effect of pletekan leaves(ruellia tuberosa) to wound closure time in rats (rattus novergicus). This research was anexperimental study with post- test design using the simple random sampling technique. Thesamples were 40 male rats with a clean incision wound along 3 cm which were divided into twogroups, control group and treatment group. The measured data were the average of woundclosure time. Data were analyzed using the mann- whitney test with 95 % confidence levelshowed a significant difference between the control group (8,45) and the treatment group (3,75)with p-value 0,000 (p<0,005). There was significant effect of ruellia tuberosa l to wound closuretime in rattus novergicus.